2012
DOI: 10.1371/journal.pone.0052891
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Organic and Conventional Crop Management on Diversity and Activity of Free-Living Nitrogen Fixing Bacteria and Total Bacteria Are Subsidiary to Temporal Effects

Abstract: A three year field study (2007–2009) of the diversity and numbers of the total and metabolically active free-living diazotophic bacteria and total bacterial communities in organic and conventionally managed agricultural soil was conducted using the Nafferton Factorial Systems Comparison (NFSC) study, in northeast England. Fertility management appeared to have little impact on both diazotrophic and total bacterial communities. However, copy numbers of the nifH gene did appear to be negatively impacted by conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 71 publications
6
29
1
Order By: Relevance
“…Further, soil respiration is considered to reflect the soil carbon availability for the microbiome. In the present study, soil respiration rates increased with organic nutrient management, while IC and control had significantly lower respiration are in accordance with previous works reported in different soil ecosystems (Enwall et al, 2007;Liu et al, 2010;Masto et al, 2006;Orr et al, 2012;van Diepeningen et al, 2006). The metabolic quotient, the ratio between respiration rate and MBC, reflects metabolically active fraction of soil microbiome.…”
Section: Impact Of Organic and Inorganic Nutrient Management Regimes supporting
confidence: 93%
See 3 more Smart Citations
“…Further, soil respiration is considered to reflect the soil carbon availability for the microbiome. In the present study, soil respiration rates increased with organic nutrient management, while IC and control had significantly lower respiration are in accordance with previous works reported in different soil ecosystems (Enwall et al, 2007;Liu et al, 2010;Masto et al, 2006;Orr et al, 2012;van Diepeningen et al, 2006). The metabolic quotient, the ratio between respiration rate and MBC, reflects metabolically active fraction of soil microbiome.…”
Section: Impact Of Organic and Inorganic Nutrient Management Regimes supporting
confidence: 93%
“…In the present study, 16S rRNA gene abundance in OM was significantly higher than in IC in 2009 and comparable in 2010, and implies that changes in bacterial community structure and abundance are often subtle (Chinnadurai et al, 2014;Drenovsky et al, 2004) and seasonal and plant growth effects often have a greater influence than those due to nutrient management processes (Moreno et al, 2009;Orr et al, 2011). Similar to our finding, He et al (2007) and Orr et al (2012) reported insignificant difference in 16S rRNA gene density between organic and inorganic nutrient management enforced soils. However, when compare to unfertilized control soil, both OM and IC having significantly higher 16S rRNA gene abundance clearly explained that the fertility source (either organic or inorganic) is the dominant factor driving the bacterial community structure (Esperschutz et al, 2007;Widmer et al, 2006) and 16S RNA gene density (Orr et al, 2011).…”
Section: Long Term Organic and Inorganic Fertility Managements Favor supporting
confidence: 84%
See 2 more Smart Citations
“…It is often hypothesized that organic agriculture promotes bacterial abundance and diversity in soil when compared with conventional systems (as observed by Lee and Yun, 2011;Liu et al, 2007;Van Diepeningen et al, 2006, for example). However, other studies found no distinguishable difference between crop management systems (Berthrong et al, 2013;Orr et al, 2012;Williams and Hedlund, 2013;Xue et al, 2013). Surprisingly, here there was no significant difference in FCM counts between organic and conventional systems, most likely because of important standard deviations.…”
Section: Application In Microbial Ecologycontrasting
confidence: 79%